Lactate biosensors for food industry - Przybyt, Małgorzata (Biotechnology and Food Science, 2014)
Lactic acid and lactate fermentation play important role in food and beverages production, control and quality. Analysis of lactate by standard methods is time, work consuming, and cannot be implemented at the production site. The alternative is the use of biosensors for lactate. The article reviews the biosensors for D- and L-lactic assay, their types, construction and application in food analysis area. The special emphasis is given to the commercial biosensor for lactate. The market survey indicates that there is a lack of lactate biosensors addressed to food industry except wine production. QUALI_JUICE project was the practical attempt to use some of the commercial biosensors in production and quality control in fruit juice industry. The results of the project indicates that commercial biosensors can be used after some minor functional adaptation in fruit juice production control. The application of these biosensors can be broadened to the other sectors of food and beverage industry.